Language Education Policy and Classroom Practice - McIntosh, Rayan Marie (Journal of Research in Vocational Education, 2026)
Language education has always been a pivotal part of global education systems, influencing personal development, cultural exchange, and international collaboration. This paper explores the key aspects of language teaching, focusing on the pedagogical strategies, the role of technology, the sociocultural influences on language learning, and the cognitive benefits associated with multilingualism. It also delves into challenges faced by language educators, the importance of teacher training, and the need for a dynamic, learner - centered approach to instruction. Lastly, the paper provides a vision for the future of language education in a digitally connected world.